Microscopic anatomy of the visceral fasciae. Issue 1 (3rd May 2017) - Stecco, Carla; Sfriso, Maria Martina; Porzionato, Andrea; Rambaldo, Anna; Albertin, Giovanna; Macchi, Veronica; De Caro, Raffaele
Abstract: The term 'visceral fascia' is a general term used to describe the fascia lying immediately beneath the mesothelium of the serosa, together with that immediately surrounding the viscera, but there are many types of visceral fasciae. The aim of this paper was to identify the features they have in common and their specialisations. The visceral fascia of the abdomen (corresponding to the connective tissue lying immediately beneath the mesothelium of the parietal peritoneum), thorax (corresponding to the connective tissue lying immediately beneath the mesothelium of the parietal pleura), lung (corresponding to the connective tissue under the mesothelium of the visceral pleura), liver (corresponding to the connective tissue under the mesothelium of the visceral peritoneum), kidney (corresponding to the Gerota fascia), the oesophagus (corresponding to its adventitia) and heart (corresponding to the fibrous layer of the pericardial sac) from eight fresh cadavers were sampled and analysed with histological and immunohistochemical stains to evaluate collagen and elastic components and innervation. Although the visceral fasciae make up a well‐defined layer of connective tissue, the thickness, percentage of elastic fibres and innervation vary among the different viscera. In particular, the fascia of the lung has a mean thickness of 134 μm (± 21), that of heart 792 μm (± 132), oesophagus 105 μm (± 10), liver 131 μm (± 18), Gerota fascia 1009 μm (± 105) and the visceral fascia of the abdomen 987 μm (± 90). The greatest number of elastic fibres (9.79%) was found in the adventitia of the oesophagus. The connective layers lying immediately outside the mesothelium of the pleura and peritoneum also have many elastic fibres (4.98% and 4.52%, respectively), whereas the pericardium and Gerota fascia have few (0.27% and 1.38%). In the pleura, peritoneum and adventitia of the oesophagus, elastic fibres form a well‐defined layer, corresponding to the elastic lamina, while in the other cases they are thinner and scattered in the connective tissue. Collagen fibres also show precise spatial organisation, being arranged in several layers. In each layer, all the fibrous bundles are parallel with each other, but change direction among layers. Loose connective tissue rich in elastic fibres is found between contiguous fibrous layers. Unmyelinated nerve fibres were found in all samples, but myelinated fibres were only found in some fasciae, such as those of the liver and heart, and the visceral fascia of the abdomen. According to these findings, we propose distinguishing the visceral fasciae into two large groups. The first group includes all the fasciae closely related to the individual organ and giving shape to it, supporting the parenchyma; these are thin, elastic and very well innervated. The second group comprises all the fibrous sheets forming the compartments for the organs and also connecting the internal organs to the musculoskeletal system. These fasciae are thick, less elastic and less innervated, but they contain larger and myelinated nerves. We propose to call the first type of fasciae 'investing fasciae', and the second type 'insertional fasciae'.